The international Trade-Union Movement : review of the International Federation of Trade-Unions. - International Federation of Trade Unions (IFTU) (Amsterdam : IFTU, 1922)
Bibliotheek E. Anseele
Periodiciteit: tweemaandelijks
Hoofdredactie: Vondelstraat 61, Amsterdam
Redactie: Edo Fimmen, L. Jouhaux, J. Oudegeest, C. Mertens
Beheer/Administratie: Vondelstraat 61, Amsterdam
Engels
Periodiek
Keywords: syndicale pers